Electric relaxation of superparamagnetic Gd-doped lead molybdato-tungstates. Issue 4 (March 2019) - Kukuła, Z.; Maciejkowicz, M.; Tomaszewicz, E.; Pawlus, S.; Oboz, M.; Groń, T.; Guzik, M.
Abstract: Tetragonal, scheelite-type Pb1–3x □x Gd2x (MoO4 )1–3x (WO4 )3x materials ( x = 0.0455, 0.0839, 0.1154, 0.1430, 0.1667 and 0.1774, where □ denotes vacancies) synthesized via solid state reaction route were magnetically and electrically examined. The ac and dc magnetic measurements as well as the Brillouin fitting procedure showed paramagnetic state with characteristic superparamagnetic-like behaviour and a spin-only contribution to the paramagnetic moment. Broadband dielectric spectroscopy studies exhibited existence in the loss spectra the faster and slower relaxation processes with various time scales for the gadolinium-poorer samples with the x vacancy parameter up to 0.1154. For samples with higher Gd content, i.e. when x > 0.1154, no signs of any relaxation processes was observed. This phenomenon has been explained by a smaller number of structural and spin defects as opposed to the samples poorer in gadolinium ions.